Implementasi Kurikulum Merdeka dalam Meningkatkan Kompetensi Profesionalisme Guru Madrasah Ibtidaiyah - Munawir, Munawir; Zubaidah, Reti; Wahyuningtias, Pinkan (ALSYS, 2025)
This research is motivated by the limited studies on the implementation of the Independent Curriculum by Madrasah Ibtidaiyah teachers, even though this phenomenon has a significant impact on the quality of learning and the transformation of basic education. The purpose of this study is to explore the understanding and practices of MI teachers in implementing the Independent Curriculum, as well as the challenges they face. The method used is qualitative research with a case study approach, involving eight MI teachers selected through purposive sampling techniques. Data were collected through in-depth interviews, classroom observations, and documentation, then analysed using thematic analysis techniques. The results of the study show four main findings: (1) the adaptation of the Independent Learning philosophy which is still technical, (2) the integration of character values ​​in learning which is not yet systematic, (3) the transformation of learning planning towards a reflective and contextual approach, and (4) limited training that does not match field needs. These findings enrich the literature on the implementation of the new curriculum and show the importance of institutional support and context-based training. The main conclusion of this study is the need to strengthen teacher capacity philosophically and practically so that the Independent Curriculum can be implemented completely and sustainably. The implications of this study include the development of contextual training policies and the importance of creating a supporting ecosystem in madrasas. This study also opens up opportunities for further studies on teacher mentoring models based on learning communities.